Performance evaluation for different data encryption algorithms on wireless sensor network (WSN) - Mhawesh, Thoalfekarali Zuhair (2018)
The Image Security primitives in the wireless sensor networks (WSN) are very energy intensive. Another problem in terms of energy consumption is added to the security of encrypted images transmitted by WSN sensor nodes. Therefore, the aim of the project is to analyse and evaluate various different algorithms used image encryption in WSN. The algorithms considered are AES, SF and SIT algorithms. The encryption algorithms are evaluated in turn by applying them to various images, separately. The performance metrics studied are the energy dissipation, execution time, and size of encryption data. The results of evaluation AES, SF and SIT algorithms in terms of encrypted data size (bytes) showed that, the SIT algorithm produce the lowest size for all encrypted Images which is below 90250bytes. AES algorithm shows the highest encrypted data size which is with above 234214 bytes. SF algorithm perform better than AES but less than SIT with close 169025 bytes. In summary, compared to the average of all the original images size (11928 bytes), all algorithms increased the image size with 1963%, 141 % 757% for AES, SF and SIT, respectively. Then the results are compared to the average energy dissipation (μJ) by applying different encryption data, AES, SF and SIT algorithms. From the results, it’s observed that SIT algorithm shows the lowest energy dissipation for all encrypted Images which is 5343392μJ. AES algorithm shows the highest energy dissipation 13865480.64 μJ. The SF algorithm located between the AES and SIT which the energy dissipation is 10006315.52 μJ. Finally, from the performance results of AES, SF and SIT algorithms in execution time (s), the SIT algorithm shows the minimum average for execution time (s) needed 0.001915s, and the AES algorithm registered the maximum average for execution time (s) needed 0.16791715s to encrypt the images before transmitted to the receiver station. The SF algorithm presented a good permanence with execution time (s) needed 0.006971s to encrypt the images before transmitted to the receiver station.